2015
DOI: 10.1002/jcb.25185
|View full text |Cite
|
Sign up to set email alerts
|

Lamin A/C Acts as an Essential Factor in Mesenchymal Stem Cell Differentiation Through the Regulation of the Dynamics of the Wnt/β‐Catenin Pathway

Abstract: Changes in the expression of lamin A/C, a fibrilar protein of the nuclear envelope, are associated with the cellular features of age-related bone loss. Reduced expression of lamin A/C inhibits osteoblastogenesis while facilitating adipogenic differentiation of mesenchymal stem cells (MSC) in vitro and in vivo. In this study we investigated the regulatory role that lamin A/C plays on the essential elements of the Wnt/β-catenin pathway, which are pivotal in MSC differentiation. Initially, we assessed the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 29 publications
4
68
0
Order By: Relevance
“…Apart from tethering to CDH2, β-catenin has also been shown to interact with lamin A/C (LMNA), a fibrillar protein of the nuclear envelope5152. In human mesenchymal stem cells (MSCs), overexpression of LMNA facilitated β-catenin entry into the cell nucleus and led to increased levels of nuclear β-catenin51 that impacted MSC differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from tethering to CDH2, β-catenin has also been shown to interact with lamin A/C (LMNA), a fibrillar protein of the nuclear envelope5152. In human mesenchymal stem cells (MSCs), overexpression of LMNA facilitated β-catenin entry into the cell nucleus and led to increased levels of nuclear β-catenin51 that impacted MSC differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…Beyond their structural function, lamins also participate in cell proliferation and differentiation through regulation of transcription and chromatin organization (Dechat et al 2008). It has been previously reported that reduced expression of lamin A/C facilitates adipogenic differentiation of mesenchymal stem cells by regulating the Wnt/β-catenin signaling pathway (Bermeo et al 2015). Reorganization of the nuclear lamina during adipocyte formation has been well described in the mouse and human model systems (Verstraeten et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…MSCs have a more robust lamin A/C network [53] and perhaps increased LINC connectivity compared to pluripotent cells. Lamin A/C increases when MSCs enter the osteogenic lineage [120], a change consistent with the increased cellular stiffness of osteoblasts [121, 122], and lamin A/C overexpression promotes osteogenic differentiation [123]. In contrast, lamin A/C decreases when MSCs undergo adipogenesis [48] and both partial and complete deletion of lamin A/C promotes an adipogenic program in MSCs [124126].…”
Section: Role Of Linc-nuclear Connections In Bone/osteoblast Phenomentioning
confidence: 99%